Utility of intraoperative magnetic resonance imaging for giant cell tumor of bone after denosumab treatment: a pilot study. (February 2022) - Furuta, Taisuke; Kubo, Tadahiko; Sakuda, Tomohiko; Saito, Taiichi; Kurisu, Kaoru; Muragaki, Yoshihiro; Adachi, Nobuo
Background: Giant cell tumor of bone (GCTB) is an intermediate but locally aggressive neoplasm. Current treatment of high-risk GCTB involves administration of denosumab, which inhibits bone destruction and promotes osteosclerosis. However, denosumab monotherapy is not a curative treatment for GCTB and surgical treatment remains required. Denosumab treatment complicates surgery, and the recurrence rate of GCTB is high (20%–30%). Purpose: To examine the utility of intraoperative magnetic resonance imaging (iMRI) for detection and reduction of residual tumor after denosumab treatment and to investigate the utility of iMRI, which is not yet widely used. Material and Methods: We enrolled five patients who received denosumab for a median period of eight months (range 6–12 months). Surgery was performed when the degree of osteosclerosis around the articular surface was deemed appropriate. We performed iMRI using a modified operation table to identify residual tumor after initial curettage and evaluated the rate of detection of residual tumor by iMRI, intraoperative and postoperative complications, exposure time of iMRI, and operation time. Results: Suspected residual tumor tissue was identified in all five cases and was confirmed by histopathology after additional curettage. The rate of detection of residual tumor by iMRI was 100%. Residual tumor was located in sites which were difficult to remove due to osteosclerosis. The iMRI was performed safely and without trouble. During the median follow-up period of 10 months (range 6–24 months), no adverse events or recurrences occurred. Conclusion: Intraoperative MRI could contribute to the reduction of residual tumor tissue and it may prevent recurrence of GCTB after denosumab therapy.